Japan 2024 - Richmond, Simon (Lonely Planet guidebooks, 2024)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime to Japan. Build a trip to remember with Lonely Planet's Japan Travel Guide. Discover popular and off the beaten track experiences from visiting Yoshino for Japan's most famous cherry-blossom-viewing festival to sipping sake at a 300-year-old brewery in Niigata and exploring the UNESCO-listed streetscapes of Hagi.--Publisher description.